Separated at birth: A comprehensive review of the Philippines’s compliance with the Constitution and related international laws concerning pregnant, nursing detainees, and the rights of their newborn infants - Chan, Kelley Ong (Animo Repository, 2021)
Unequal treatments towards women have long been existent. This calls attention to the vulnerability and needs of certain women in jail. Jail facilities have long been tailored exclusively for male detainees despite the increasing number of minority groups. In the case of pregnant or nursing detainees, they are entitled to the presumption of innocence and the right to life and health, which extends to the innocent infant born to them, which is especially weighty for pregnant detainees who carry another life inside them. It becomes not just a matter of one life but two. Their rights must be intact and protected under the Constitution. International laws have provided the required treatment towards detainees and prisoners. Specifically, for pregnant and nursing detainees, there exists the Mandela Rules and Bangkok Rules. The more updated jail operations of foreign countries were utilized for comparison in this paper. In the local context, limited studies have been made towards Philippine detainees and the operation of detention centers, with the scant information leading to misconceptions and lack of awareness. Thus, this paper conducted interviews with detainees and the jail staff for better understanding and found that facilities as well as access to services in Philippine jails are not standardized and require assessment processes. Moreover, the inconsistencies of jail procedures in different places shows gaps in services of the system. The lack of proper and specified laws and manuals towards these women—especially for vulnerable ones like those pregnant and nursing, diminishes their rights and dignity as human beings, which also influences the rights of their offspring. The insufficiency of jail facilities to properly implement its operations construes noncompliance with international standards that the country adheres to even at the minimal level, prejudicing the rights of pregnant and nursing detainees as well as their children.